PEMANFAATAN MEDIA VISUAL DALAM OPTIMALISASI RUANG MEMBACA UNTUK MENINGKATKAN LITERASI SISWA DI SMA 1 PADARINCANG KABUPATEN SERANG - Husni, Mohamad; Lestari, Dini Martinda; Anggriawan, Muhammad Angga; Handayani, Novi; Sembiring, Evi Dora (Yayasan Education and Social Center, 2024)
Community service activities at SMA 1 Padarincang, Serang Regency, focus on the use of visual media in optimizing the reading room to increase student literacy. The results of this activity show various positive impacts. The use of attractive and interactive visual media has succeeded in increasing students' reading interest and literacy skills. Learning videos, visual presentations and animations create a more engaging and effective learning experience. Intensive training for teachers also resulted in improved learning quality with teachers becoming more skilled in designing interactive materials. The innovative reading room redesign creates a dynamic learning environment and supports collaborative and independent learning. In addition, community involvement in this activity increases participation and support for educational changes in schools. Related research shows that the integration of visual media in learning can increase students' motivation and understanding of subject matter, as well as confirming the importance of collaboration between schools and communities in improving the quality of education. Thus, the use of visual media in the reading room has great potential to improve literacy and the quality of learning at SMA 1 Padarincang and other schools